2014
DOI: 10.30971/pje.v31i1.80
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Early Childhood Education in Public and Private Sector Schools

Abstract: This study was designed to compare the situation of Early Childhood Education (ECE), provided in public and private sector schools. The major objectives of the study were to evaluate the learning abilities of the students who were receiving early childhood education, to study demographic variations of students in relation with their learning ability and to study availability of physical facilities in the public and private sector schools for early childhood education. In this study, data of 100 respondents was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…According to the first objective of the study, it is revealed that physical facilities of public sector schools were greater than in private sectors schools. Nazir & Khurshid (2014) found that there was a lack of physical facilities for ECE in private and public-sector schools.…”
Section: Discussionmentioning
confidence: 99%
“…According to the first objective of the study, it is revealed that physical facilities of public sector schools were greater than in private sectors schools. Nazir & Khurshid (2014) found that there was a lack of physical facilities for ECE in private and public-sector schools.…”
Section: Discussionmentioning
confidence: 99%
“…Various researches were conducted to explore the facilities of ECE in Punjab i.e. " ( Arshad and Zamir, 2018;Bhatti, 2007;Bhutta, 2020;Shakeel andAslam, 2019, Naz, Yousaf, andArshad, 2019). The study conducted by Saif, inam and Abiodullah, (2020) explored the current status of katchi class concerning early childhood education policies and practices in Punjab.…”
Section: Discussionmentioning
confidence: 99%
“…Besides it, ECE is not organized at the international level in Punjab by the administration. According to Arshad and Zamir (2018 ), Saif, Inam & Abiodullah (2020),Shakeel and Aslam (2019),Naz, Yousaf, and Arshad, (2019) ECE in Punjab are not up to the satisfactory level despite implementing Punjab ECE policy 2017. The primary reason for failure is poor coordination between the School Education Department (SED) and government schools.…”
mentioning
confidence: 99%
“…Generally, degree of parent's engagement has been under question and this has been studied worldwide. However, this study has been specifically pointed on parental involvement in early childhood education and preschool academics (Naz, Yousaf, & Arshad, 2020), subsequently gauging how it improves the learning of a student. The study will discuss research findings related to role of parents, importance of stakeholders and belief of parents during early years of child and the hurdles which dilute parental attention towards child's grooming at early age (Cosmas, 2018).…”
Section: Introductionmentioning
confidence: 99%